Sprawozdanie z obrad VIII Forum Kultury Słowa "Kultura zachowań językowych Polaków", które odbyło się 20-22.10.2011 r. w Rzeszowie - Krauz, Maria (Słowo. Studia językoznawcze, 2011)
From 20th until 22nd October 2011 at the University of Rzesz6w was held VIII Forum on Word Culture devoted to culture of a language behaviour of Polish people. It was organised by the Council for the Polish Language at the Presidium of the Polish Academy of Science and the University of Rzeszéw. The conference was an important intellectual event, giving an opportunity to have an interesting discussion about a language communication in Poland in the era of transformation. The discussion concerned: a culture of behaviour in historical, anthropological and political context, language communication in different social circles, communication strategies, a language etiquette and a language of politics. The varied, but coherent subject matter created an opportunity to have a discussion for each of the Forum participants, because speakers and disputants participated in sessions on equal terms. About 300 people took part in the sessions of the Forum. The speakers were the most outstanding experts on the discussed subject matter, inter alia: Prof. Anna Dabrowska, Prof. Malgorzata Marcjanik, Prof. Halina Zgétkowa, Prof. Jolanta Antas, Prof. Elzbieta Umiriska-Tyton, Prof. Stanistaw Dubisz, Prof. Jan Doroszewski, Prof. Kazimierz 026g, Jagoda Bloch, PhD, Jakub Pstrag, PhD, Rafat Zimny, PhD, Przemystaw Zukiewicz, PhD, Agnieszka Choduh, PhD, Elzbieta Kucharska-Dreiss, PhD. A panel discussion was conducted by: Prof. Jerzy Bralezyk, Prof. Mirostaw Karwat, Katarzyna Kiosifiska, PhD, Jerzy Sosnowski, and sessions in sections were conducted by: Prof. Andrzej Maralery Pisarek, Prof. Zofia Bilut-Homplewicz, Prof. Kazimierz Ożóg. The sessions were very popular among students and language enthusiasts from Rzeszów.